2020
DOI: 10.3389/fmicb.2020.01294
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Antibiotic and Heavy Metal Resistance and Sequence Type Diversity of Vibrio parahaemolyticus Isolated From Penaeus vannamei at Freshwater Farms, Seawater Farms, and Markets in Zhejiang Province, China

Abstract: Vibrio parahaemolyticus is the leading cause of seafood-borne bacterial poisoning in China and is a threat to human health worldwide. The aim of this study was to assess the antibiotic resistance profiles and distribution of heavy metal resistance of V. parahaemolyticus isolates from Penaeus vannamei from freshwater farms, seawater farms, and their corresponding markets in Zhejiang, China and to assess the relationship between multidrug resistance (MDR) and multi-heavy metal resistance (MHMR). Of the 360 P. va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The correlation was considered strong if the r ≥ 0·6, moderate if the r value was between 0·4 and 0·6, and weak if r < 0·4 (Jiang et al . 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The correlation was considered strong if the r ≥ 0·6, moderate if the r value was between 0·4 and 0·6, and weak if r < 0·4 (Jiang et al . 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in our study, all the isolated bacterial species showed some level of resistance against tested antibiotics which supported our hypothesis that bacteria resistant to heavy metals would also be able to resist antibiotics. Cooccurrence of heavy metals resistance and antibiotic resistance is well reported (Yamina et al 2012;Jiang et al 2020;Thomas et al 2020). The microorganisms that have developed both heavy metals and antibiotic resistance in contaminated environments can act as pool for the resistance genes that can ultimately be acquired by the pathogenic species.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of V. cholerae to antimicrobials and HMs has been previously reported ( Song et al., 2013 ; Bhuyan et al., 2016 ; Baron et al., 2017 ; Sulca et al., 2018 ; Xu et al., 2019 ). On the other hand, a very important aspect to consider is that HMs tolerance was prevalent in the V. parahaemolyticus strains with more than two AR phenotypes ( He et al., 2016 ; Kang et al., 2018 ; Jiang et al., 2020 ).…”
Section: Impact Of Seawater Pollution In Bivalves and Vibri...mentioning
confidence: 99%